2021
DOI: 10.1186/s12951-021-01078-x
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared light-triggered nano-prodrug for cancer gas therapy

Abstract: Gas therapy (GT) has attracted increasing attention in recent years as a new cancer treatment method with favorable therapeutic efficacy and reduced side effects. Several gas molecules, such as nitric oxide (NO), carbon monoxide (CO), hydrogen (H2), hydrogen sulfide (H2S) and sulfur dioxide (SO2), have been employed to treat cancers by directly killing tumor cells, enhancing drug accumulation in tumors or sensitizing tumor cells to chemotherapy, photodynamic therapy or radiotherapy. Despite the great progress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 233 publications
0
20
0
Order By: Relevance
“…Cancer is currently one of the most common causes of death worldwide. To effectively treat cancer, researchers have tried a variety of treatments including gene therapy, chemotherapy, , radiotherapy, , and gas therapy. As an emerging treatment, gas therapy uses gas transmitters to induce tumor cell death. Studies have found that several gas molecules, such as nitric oxide (NO), carbon monoxide (CO), oxygen (O 2 ), and hydrogen sulfide (H 2 S), could regulate the process of cancer. Among them, NO was the first found gaseous biochemical messenger, and it played a dual role in tumor progression: low concentrations of NO might promote tumor growth, while high concentrations of NO (>1 μM) could induce tumor cell apoptosis through multiple pathways .…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is currently one of the most common causes of death worldwide. To effectively treat cancer, researchers have tried a variety of treatments including gene therapy, chemotherapy, , radiotherapy, , and gas therapy. As an emerging treatment, gas therapy uses gas transmitters to induce tumor cell death. Studies have found that several gas molecules, such as nitric oxide (NO), carbon monoxide (CO), oxygen (O 2 ), and hydrogen sulfide (H 2 S), could regulate the process of cancer. Among them, NO was the first found gaseous biochemical messenger, and it played a dual role in tumor progression: low concentrations of NO might promote tumor growth, while high concentrations of NO (>1 μM) could induce tumor cell apoptosis through multiple pathways .…”
Section: Introductionmentioning
confidence: 99%
“…With the progress of clinical trials, hydrogen therapy is considered a promising antitumor strategy. Hydrogen has been widely demonstrated to have anti‐inflammatory and anticancer effects, [ 10 ] showing important functions in the regulation of homeostasis in vivo, including selective treatment of diseased cells while protection of normal cells; [ 11 ] and selective antioxidant is a commonly accepted mechanism in hydrogen therapy. [ 12 ] For cancer cells, both elevation and decrease of properly overexpressed reactive oxygen species (ROS) can lead to cancer cell damage and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Varieties of compounds have been approved for therapeutic and imaging purposes in the clinical. Up to now, they have a wide range of applications in cancer treatment, which has been considered as promising agents, including chemotherapy, photodynamic therapy and imaging guided treatment [ 3 ]. Metal complexes represented by cisplatin exhibited the broad spectrum of antitumor activity, and still act as the first-line drugs in the clinical tumor treatment.…”
Section: Introductionmentioning
confidence: 99%